If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 28)(4x + 10) = 0 Reorder the terms: (28 + 2x)(4x + 10) = 0 Reorder the terms: (28 + 2x)(10 + 4x) = 0 Multiply (28 + 2x) * (10 + 4x) (28(10 + 4x) + 2x * (10 + 4x)) = 0 ((10 * 28 + 4x * 28) + 2x * (10 + 4x)) = 0 ((280 + 112x) + 2x * (10 + 4x)) = 0 (280 + 112x + (10 * 2x + 4x * 2x)) = 0 (280 + 112x + (20x + 8x2)) = 0 Combine like terms: 112x + 20x = 132x (280 + 132x + 8x2) = 0 Solving 280 + 132x + 8x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4'. 4(70 + 33x + 2x2) = 0 Factor a trinomial. 4((14 + x)(5 + 2x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(14 + x)' equal to zero and attempt to solve: Simplifying 14 + x = 0 Solving 14 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + x = 0 + -14 x = 0 + -14 Combine like terms: 0 + -14 = -14 x = -14 Simplifying x = -14Subproblem 2
Set the factor '(5 + 2x)' equal to zero and attempt to solve: Simplifying 5 + 2x = 0 Solving 5 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = 0 + -5 2x = 0 + -5 Combine like terms: 0 + -5 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5Solution
x = {-14, -2.5}
| -3x+1=-2(3x+10) | | 2w^2+2w=34 | | 5r+15=2.25r | | 3(6+x)=30 | | 3x+4-2-x=14 | | -3(e+4)=4w-5 | | -3+2x=-x-6 | | 1-6x=5-4x | | 22-44= | | 13x+9=-15 | | 2a+4.2=3a-16 | | 2y+4=26 | | XY=98 | | 12p=-4 | | -6n+7n+4= | | 5k+8(k-4)=-84 | | 4x-7=x-34 | | 5y-5=7y+9+10y+4 | | -11=1+8k | | k*(-9k)*k=0 | | X(3x-5)=(3x+8)(x-5) | | 3+2(3n+2)=41 | | 11x+13(19-x)=211 | | -9t(t-2)=4(t-15) | | 2y+120=180 | | 4b=120-5t | | 2b+5=b+10 | | 52=(3x+2) | | 3(x+3)+x=2(x+3)-5 | | 9x^2+27x=7 | | y=3x^2-7x-1 | | 0.2(x-2)-0.4(x+2)=-0.2x-0.4 |